Early detection and prevention of stress and fatigue in elite athletes: The use of psychological and clinical measurement instruments - Theriault, D.; Lacoste, E.; Gadoury, M.; Richard, D.; Tremblay, A.; Labrie, A.; Leblanc, C.; Theriault, G. (Medicine & Science in Sports & Exercise, 1995)
A psychological stress measurement tool and a clinical checklist to evaluate fatigue symptoms were completed periodically during a 10-month training program by 23 elite swimmers. The sensitivity to fatigue states of both tools was related. Higher scores were associated with greater fatigue and stress ratings as well as differences in resting plasma catecholamines. Implication: Psychological tools are valuable for assessing stress and fatigue in athletes undergoing serious training. They have the potential to be used alone as analytical tools or as cross-validation tools for other measures of detrimental trained states.